Tax Planning in Business Purchase Agreements, with Sample Clauses - Kent D. Kehr; Gene M. Zafft (Washington University Law Quarterly, 1958)
The success or failure of the small- or medium-sized business is dependent primarily upon the ability of its "key-men," who are generally the owners of the business. The death or retirement of one of these men, therefore, if not provided for, can cause havoc with the business to the detriment of the remaining shareholders or partners. This Article will consider the tax problems raised by the death of a stockholder and the death or retirement of a partner and the most practical and beneficial methods of anticipating and meeting those problems.
Keywords: Corporate taxes; Taxation -- United States; Urban transportation -- Federal aid; Partnerships